ANALISIS FAKTOR KEAMANAN DALAM KETERSEDIAAN FITUR BAGI PENGGUNA MOBILE BANKING - Alfhira (2022)
Mobile banking or m-banking is 'everything' as today's information technology makes it easier for customers to transact. In addition to making it easier for mobile banking transactions, it has various security features in mobile banking that are owned by every bank that has mobile banking services. Security is an important factor in increasing trust. Because when communication devices such as cellular phones are connected to the internet, they are very vulnerable to security, therefore every bank has the availability features of the security factor of the mobile banking users. The author's purpose is to find out what security features are available for each bank that has Mobile Banking services to attract the interest of Mobile Banking users and what are the advantages and disadvantages of each bank on the security of Mobile Banking services. The results of the questionnaire collected 104 respondents from the community who have or do not have Mobile Banking, from the age of 17 to over 55 years who fill out the questionnaire on average know what features are contained in the Mobile Banking service used. The security features in a Mobile Banking service are almost the same but differ in the mention of names, the average respondent uses the Password security feature or biometric feature that makes the transaction easier.